2005
DOI: 10.1128/jcm.43.3.1269-1277.2005
|View full text |Cite
|
Sign up to set email alerts
|

LeishmaniaPromastigote Membrane Antigen-Based Enzyme-Linked Immunosorbent Assay and Immunoblotting for Differential Diagnosis of Indian Post-Kala-Azar Dermal Leishmaniasis

Abstract: Diagnosis of post-kala-azar dermal leishmaniasis (PKDL), caused by Leishmania donovani, is difficult, as the dermal lesions are of several types and resemble those caused by other skin diseases, especially leprosy. Since the disease generally appears very late after the clinical cure of kala-azar in India, it is also difficult to correlate PKDL with a previous exposure to L. donovani. Very few attempts have been made so far to diagnose PKDL serologically, and the diagnostic methods vary in their sensitivities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 56 publications
4
22
0
Order By: Relevance
“…This result agrees with previous studies that also demonstrated an increased sensitivity of the assays when homologous instead of heterologous antigens were used (25)(26)(27).…”
Section: Discussionsupporting
confidence: 95%
“…This result agrees with previous studies that also demonstrated an increased sensitivity of the assays when homologous instead of heterologous antigens were used (25)(26)(27).…”
Section: Discussionsupporting
confidence: 95%
“…Our preliminary observation of a significant elevation of the percentage of the population of CD4 ϩ CD25 ϩ T cells in VL in comparison to healthy controls, its decline at cure, and further significant elevation in PKDL patients indicate that in vivo expansion and suppressive activity of CD4 ϩ CD25 ϩ T cells is probably influenced by the production of IL-10 and TGF-␤. More interestingly, IgA production in the different PKDL patients followed the pattern of enhanced IL-10 and TGF-␤ production with disease severity and appears to confirm our earlier speculation that the elevation of IgA in some PKDL patients might be induced by IL-10 with help from TGF-␤ (46).…”
Section: Discussionsupporting
confidence: 70%
“…IL-10 and TGF-␤ are involved in enhancing IgA production in human cells (59 -61). Earlier, we reported an up-regulation of IgA in some of the PKDL patients (46) and postulated that this up-regulation might be correlated with enhanced IL-10 production. In this study we show that PKDL patients with up-regulated serum IgA in fact produce high amounts of IL-10 in vitro under stimulation with LAg ( Fig.…”
Section: Immune Response In Pkdl Patients Is Definitely Correlated Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Though not very sensitive (44%), Leishmania-specific immunoglobulin E (L-IgE) has been suggested to be a specific (98.3%) marker of active VL disease (L. chagasi), although it is undetectable at subclinical levels in VL patients, Chagas disease patients, and healthy controls (143)(144)(145). Moreover, increased L-IgE concentrations were demonstrated to regress to normal values during the time span of treatment (143,145,146). In cases of atypical cutaneous leishmaniasis, IgE levels were not significantly different from those of asymptomatic or healthy controls (147).…”
Section: Identified Biomarkersmentioning
confidence: 99%